Characterization of rice flour and pastes with different sweeteners for extrusion‐based 3D food printing. Issue 6 (1st July 2022) - Prithviraj, V.; Thangalakshmi, S.; Arora, Vinkel Kumar; Liu, Zhenbin
Abstract: This work aims at investigating the impact of commonly used sweeteners—sugar and jaggery on 3D printability of rice flour (RF) paste. The physicochemical characteristics of rice flour suitable for 3D food printing have been investigated. Three mixes, rice flour with water ( M 1 : RF—50.86%, water—49.14%), rice flour with sugar and water ( M 2 : RF—36.75%, sugar—14.10%, water—49.14%) and rice flour with jaggery and water ( M 3 : RF—36.75%, jaggery—14.10%, water—49.14%) were compared on 3D printability based on visual inspection and properties supporting 3D printability and shape retention. The effect of the three mixes was characterized on color, rheological, thixotropic, and handling properties. Out of the three mixes, M 3 is found to have the best printability characteristics with shear thinning behavior, yield stress of 157 Pa, flow stress of 121 Pa, and extrusion force of 6.62 kg. Abstract : This article has compared the different traditional sweeteners for their possible use in 3D food printing. It has been found that jaggery offers more viscoelastic properties suitable for 3D food printing. Various properties have been compared to prove the suitability of jaggery as a 3D printable material.